OSCI: an organisational and safety climate inventory - Silva, S. A.; Lima, M. L.; Baptista, C. (Safety Science, 2004)
After 20 years of research on safety climate, the study of the relationship between safety climate and organisational climate has just begun and has not been fully explored. In this paper, a questionnaire is presented, OSCI (Organisational and Safety Climate Inventory), to address the characterisation of both organisational climate and safety climate. This instrument comprises 78 items and includes the Organisational Climate Questionnaire and the Safety Climate Questionnaire (Safety as an Organisational Value Scale, Content of Safety Climate Scale, Organisational Safety Practices Scale and Personal Involvement with Safety Scale). Two studies tested the psychometric properties of OSCI. In the first study, six independent judges rated the validity of the scales with the Competing Values Model (Quinn, 1988). The results of this study revealed that these items had good construct validity. A second study was developed to test OSCI's reliability and predictive validity with data collected in 15 industrial organisations, from a total of 930 workers. The results of the final version of the scale supported the instrument's reliability and predictive validity.